1997
DOI: 10.1002/j.1550-8528.1997.tb00283.x
|View full text |Cite
|
Sign up to set email alerts
|

The Human Obesity Gene Map: The 1996 Update

Abstract: An update of the human obesity gene map up to October 1996 is presented. Evidence from Mendelian disorders exhibiting obesity as a clinical feature, single-gene mutation rodent models, quantitative trait loci uncovered in crossbreeding experiments with mouse, rat, and pig models, association and case-control studies with candidate genes, and linkage studies with genes and other markers is reviewed. All chromosomal locations of the animal loci are converted into human genome locations based on syntenic relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…dence on complex inheritance without a database (e.g., Duffy, 1997;Perusse et al, 1997). Internet gives a general asthma database (http://cooke.gsf.de).…”
Section: Methodsmentioning
confidence: 99%
“…dence on complex inheritance without a database (e.g., Duffy, 1997;Perusse et al, 1997). Internet gives a general asthma database (http://cooke.gsf.de).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatic complications in obese children have been reported, particularly hepatic steatosis characterized by raised serum transaminase levels (124). Abnormal liver enzymes may be associated with cholelithiasis, but this condition is rare in children and adolescents.…”
Section: Hepatic and Gastric Complicationsmentioning
confidence: 99%
“…Several types of research have been used to identify these genes and the specific DNA sequence variation responsible for the increase in risk of becoming obese. The evidence accumulated so far has recently been reviewed (124) and provides statistical or experimental support for a role for about 70 genes, loci or markers. Many more years of research will be needed before the important genes and critical mutations are finally identified for both excess body fat content and upper body and abdominal fat accumulation.…”
Section: Types Of Genetic Effectsmentioning
confidence: 99%
“…Among the genetic factors, polymorphism or mutations in any of the following genes may be involved in the pathophysiology of obesity: badrenergic receptor, tumor necrosis factor (TNF), pro-opiomelanocortin (POMC), neuropeptide Y (NPY), NPY-receptor, melanocortin receptor (MC4R), leptin, and leptin receptor. 3 Severe obesity is associated with a higher likelihood of continued overweight. This risk is much higher in children with obese parents.…”
Section: Introductionmentioning
confidence: 99%